2015
DOI: 10.5817/bse2015-1-5
|View full text |Cite
|
Sign up to set email alerts
|

A walk through the multimodal landscape of university websites

Abstract: The study provides an insight into the ways in which universities employ multimodal elements to advertise the academic experience, research-informed teaching and research results, thus attracting prospective students. Anchored in the methodology of genre analysis and multimodal discourse analysis related to Hallidayan Systemic Functional Linguistics, the research focuses on the contribution of images -photographs and pictures -to the ideational, interpersonal and textual meanings conveyed by the websites to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…Regarding universities' websites and webpages, different studies have examined different aspects of language, usage, and application in various settings for the purpose of understanding this genre in comparison with other academic disciplines. Tomarkova (2015), for example, explored the websites of some Czech, British, and American universities to compare and contrast their multimodal features. He found that cultural and social contexts affect the universities' representation.…”
Section: Academic Genresmentioning
confidence: 99%
“…Regarding universities' websites and webpages, different studies have examined different aspects of language, usage, and application in various settings for the purpose of understanding this genre in comparison with other academic disciplines. Tomarkova (2015), for example, explored the websites of some Czech, British, and American universities to compare and contrast their multimodal features. He found that cultural and social contexts affect the universities' representation.…”
Section: Academic Genresmentioning
confidence: 99%
“…Universities use their websites to project their values and beliefs about elements of their overall institutional structures, which include their social, pedagogical and curricular structures. Previous research has shown that university website designs are informed by an array of strategies to represent a carefully curated institutional identity, and the information displayed on website webpages often reveals messages that align with the institutional value systems, and by extension, a hidden curriculum (Killick, 2016;Lažetić, 2019;Tomášková, 2015;Wymer & Thiele, 2016;Zhang & O'Halloran, 2012).…”
Section: Hidden Curriculum: Value Systemsmentioning
confidence: 99%
“…All accredited Teacher Education programs must demonstrate an enhanced focus on themes of special education and diversity in their developments of TE programs, which include but are not limited to the course selections, the practicums, and the values underpinning their pedagogical principles. However, universities have the discretion to place more or less emphasis on different features of inclusivity in education -which they often do (Crocker & Dibbon, 2008) -to complement their university's value systems and brand profile (Lažetić, 2019;Tomášková, 2015;Zhang & O'Halloran, 2013). The representation and implementation of initiatives aimed at promoting inclusivity in education by Education faculties in universities are particularly important to in making the hidden curriculum detectable as teachers play a major role in mediating its negative impact on learners' prospects for success (Apple, 2011;Pantić & Florian, 2015).…”
Section: Value System One: Inclusive and Diverse Teachingmentioning
confidence: 99%
See 2 more Smart Citations